Enhanced Cardiomyocyte Function in Hypertensive Rats With Diastolic Dysfunction and Human Heart Failure Patients After Acute Treatment With Soluble Guanylyl Cyclase (sGC) Activator - Kolijn, Detmar; Kovács, Árpád; Herwig, Melissa; Lódi, Mária; Sieme, Marcel; Alhaj, Abdulatif; Sandner, Peter; Papp, Zoltán; Reusch, Peter H.; Haldenwang, Peter; Falcão-Pires, Ines; Linke, Wolfgang A.; et al. (Frontiers in Physiology, 2020)
Aims: Our aim was to investigate the effect of nitric oxide (NO)-independent activation of soluble guanylyl cyclase (sGC) on cardiomyocyte function in a hypertensive animal model with diastolic dysfunction and in human biopsies from heart failure with preserved ejection fraction (HFpEF) patients using the sGC activator, BAY 58-2667 (cinaciguat). Methods: Dahl salt-sensitive (DSS) and control rats were fed a high‐salt diet for 10 weeks and then acutely treated in vivo with the sGC activator BAY 58-2667 for 30 minutes. Then single skinned cardiomyocyte passive stiffness (Fpassive) was determined. Titin phosphorylation, inflammatory and hypertrophic signalling pathways including NO/sGC/cGMP/PKG, protein kinase (PK)A, calcium-calmodulin kinase II (CaMKII), extracellular signal-regulated kinase 2 (ERK2) and PKC were assessed. We also explored the contribution of pro-inflammatory cytokines and oxidative stress levels to the modulation of Fpassive. Immunohistochemistry and electron microscopy were used to assess the translocation of sGC and connexin-43 proteins in these rats. Results: High Fpassive was found in rats and human biopsies compared to control groups, mainly attributed to titin hypophosphorylation and deranged site-specific phosphorylation of elastic titin regions. This was accompanied by lower levels of PKG and PKA activity, along with dysregulation of hypertrophic pathway markers. DSS rats and human biopsies showed higher pro-inflammatory cytokines and oxidative stress compared to controls. DSS animals benefited from treatment with the sGC activator, as Fpassive, titin phosphorylation, PKG and the hypertrophic pathway kinases, pro-inflammatory cytokines, and oxidative stress all significantly improved. Immunohistochemistry and electron microscopy revealed a translocation of sGC protein towards the intercalated disc following treatment, in both control and DSS samples, which was confirmed by the gap junction protein connexin-43 staining at the intercalated disk. DSS rats showed a disrupted connexin-43 pattern and partially improved after the treatment. In HFpEF biopsies, the high Fpassive, reduced titin phosphorylation, dysregulation of the NO-sGC-cGMP-PKG pathway and kinases activity were all improved by sGC treatment, and accompanied by reduced pro-inflammatory cytokines and oxidative stress. Conclusion: Our data show that sGC activator improves Fpassive, reduces inflammation and oxidative stress, improves sGC-PKG signalling and normalizes hypertrophic kinases, indicating that it is a potential treatment option for HFpEF patients.